KEBIJAKAN ALIH MANFAAT COVID-19 DALAM MANFAAT JAMINAN KESEHATAN NASIONAL - Gilbert Renardi Kusila; Endang Suparniati; Tonang Dwi Ardyanto; Donald Pardede; Firdaus Hafidz; Wan Aisyiah Baros; Dedy Revelino; Erzan Dhanalvin; Benyamin Saut; Citra Jaya; Ayunda Oktavia (Jurnal Jaminan Kesehatan Nasional, 2022)
Since the COVID-19 pandemic occurred at the end of January 2020, the health social security administering body (BPJS Kesehatan) as the payer has an important part in handling COVID-19, namely by carrying out the process of verifying claims for COVID-19 cases while the financing is carried out by Ministry of Health. However, COVID-19 benefits may be transferred to the National Health Insurance benefits during the endemic period. Therefore, this study aims to evaluate services and obtain policy recommendations for the transfer of COVID-19 benefits. Qualitative research through focus group discussions was conducted in September 2021 with policymakers, clinicians, COVID-19 survivors, and BPJS Kesehatan. The results of the qualitative study show that there are still many obstacles in the service process. Therefore, it is necessary to regulate the provisions of service regulations. As for the claim process, health facilities find it difficult to change the dynamic regulations during the pandemic. BPJS Kesehatan requires policy certainty to determine the end of the pandemic period. If the COVID-19 benefits are transferred to JKN after the pandemic, the source of financing may not only be done through the conversion of contributions but there is also an option for assistance funds from the government. In terms of tariffs, it is necessary to calculate costs according to the agreed benefit package through INA-CBG. Gradual and thorough preparations are needed for the implementation of the transfer of COVID-19 benefits in the benefits of JKN.